Medieval saints and modern screens : divine visions as cinematic experience (2017)
At the age of six, I took a vow of silence. I had witnessed something so exquisite, so evanescent that I had to memorialize it. I had to sacrifice my words on the altar of something greater than myself. What engendered this act? The impossible purity of love shared by a singing bibliophile and a bestial curmudgeon. I had just seen Beauty and the Beast (Gary Trousdale and Kirk Wise, 1991) at the cinema. In the dark embrace of a nondescript multiplex on an otherwise forgotten afternoon, I had seen – and felt – the truth of the universe, or so it seemed. It was, for want of a better word, mystical. Sure, the singing teapot didn’t hurt my complete and overwrought devotion to the film. And I had to abandon my silence a few hours later, so as to stop annoying my Mum. But still. For those brief few hours, I ascended the lofty heights of knowledge of how to be human, how to be in the world, and perhaps most importantly how, eventually, I would be an adult. I was in the film; the film was in me. The principal contentions formulated in this book lie in the crux of that experience, and are threaded through the analyses in the pages that follow. I maintain that medieval mystical episodes are made intelligible to modern audiences through reference to the filmic – the language, form, and lived experience of cinema. Similarly, reference to the realm of the mystical affords a means to express the disconcerting physical and emotional effects of watching cinema. Moreover, cinematic spectatorship affords, at times, a (more or less) secular experience of visionary transcendence: an ‘agape-ic encounter’. This transcendent experience is functionally identical to the episodes of ecstasy which are the mainstay of medieval hagiography. This is not to say that all moviegoers are, actually, Catholic mystics, if only they knew it. Rather, I attest that our use, enjoyment, and conceptualization of cinema – and more recently, three-dimensional virtual environments online – reflect our enduring preoccupation with those topics which were previously the domain of religion, and thus hagiography.